Global health landscape challenges triggered by COVID-19 - Hiroki Nakatani; Kei Katsuno; Hayato Urabe (BMC, 2020)
Abstract The COVID-19 pandemic highlighted the vulnerability of every aspect of the globalized world, including R&D. Potentially critical R&D areas have been neglected because of the lack of market-driven incentives. However, new initiatives are emerging to address the present crisis of COVID-19 and possibly future similar incidents that will threaten humanity. In this paper, the global health landscape of R&D is discussed in terms of research focus and funding, illustrating under-funding in communicable diseases with the exception of three major infections: HIV/AIDS, tuberculosis, and malaria. The initiatives triggered by the COVID-19 pandemic and the novel emphasis on "access" are discussed. Finally, the authors propose a new funding model to address R&D in the case of market failure, by forming alliance between government, industry, and international philanthropic organization (GHIT model), and define clear strategy of enhancing access as the way forward.